PERBANDINGAN EFEK LATIHAN TENDANGAN BOLA BERGERAK DAN TETAP TERHADAP HASIL TENDANGAN KE ARAH GAWANG PADA SEKOLAH SEPAK BOLA (SSB) CONDROMOWO KETANGGI - Pandu Panata Dwi Cahya; Agam Akhmad Syaukani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sports are very important for human body health, one of the most popular sports among the Indonesian people is football. Football in Indonesia has developed significantly throughout the country, many football enthusiasts train in this game from an early age, as seen in several regions. One of the developments in football can be seen from the existence of Football Schools in Indonesia, one of which is the Condromowo Ketanggi Football School. One of the movements or exercises that are often performed is kicking towards the goal, which aligns with the objective of this game, which is to score as many goals as possible against the opponent's goal. Therefore, training in kicking the ball towards the goal is conducted. In this study, two types of kicking exercises are carried out, namely moving ball kicks and stationary ball kicks. The aim is to train each player's ability to score. From the results of the experiments and research conducted, the training implemented on the SSB Condromowo Ketanggi students has shown a very significant improvement, making this training very good for enhancing the kicking skills of soccer players. This significant improvement is indicated by the T-Test results with a significance value of < 0.5